2010
DOI: 10.1002/art.27756
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of tolerogenic dendritic cells in established collagen‐induced arthritis is associated with a reduction in Th17 responses

Abstract: Results. Tolerogenic DCs displayed a semimature phenotype, produced low levels of inflammatory cytokines, and exhibited low T cell stimulatory capacity. Upon intravenous injection into arthritic mice, tolerogenic DCs migrated to the spleen, liver, lung, feet, and draining lymph nodes. Treatment of arthritic mice with type II collagen-pulsed tolerogenic DCs, but not unpulsed tolerogenic DCs or mature DCs, significantly inhibited disease severity and progression. This improvement coincided with a significant dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(122 citation statements)
references
References 52 publications
8
114
0
Order By: Relevance
“…DC have the homeostatic function of promoting immunological tolerance to self‐antigens thereby preventing the development of autoimmune disorders 65. Both pre‐clinical and clinical studies have shown that adoptively transferred DC have potent immunosuppressive properties 14, 66, 67, 68. However, there is a risk that DC placed in the pro‐inflammatory environment of the host with active autoimmune disease would convert to activated self‐antigen‐presenting DC, promoting immunity rather than tolerance, thereby worsening the disease.…”
Section: Discussionmentioning
confidence: 99%
“…DC have the homeostatic function of promoting immunological tolerance to self‐antigens thereby preventing the development of autoimmune disorders 65. Both pre‐clinical and clinical studies have shown that adoptively transferred DC have potent immunosuppressive properties 14, 66, 67, 68. However, there is a risk that DC placed in the pro‐inflammatory environment of the host with active autoimmune disease would convert to activated self‐antigen‐presenting DC, promoting immunity rather than tolerance, thereby worsening the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, expression of glucocorticoid-inducible TNFR (GITR) has been shown to occur in protective Treg cells (22). Induction of smDC has to date been experimentally achieved by DC stimulation under diminished inflammatory environments, such that are achieved by added vitamin D (23,24), , estrogen (25), MyD88 inhibitors (26), and IL-10 (27).…”
Section: Endritic Cells (Dc) Undergo Transition From Immature DCmentioning
confidence: 99%
“…+ Treg cells. Immature DCs are considered to be prototypic tolerogenic DCs due to their poor T cell stimulatory capacity (40). Immature DCs have therefore been utilized to induce immunosuppression in mammals with specific malignancies or autoimmune disease, as well as following transplantation (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%